Pengaruh Dana Pihak Ketiga Dan Manajemen Risiko Terhadap Kinerja Keuangan Bank Pembiayaan Rakyat Syariah Di Indonesia - Nuraeni Nuraeni; Lita Murdiana; Khoirul Huda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Banking, which acts as a financial middleman, is crucial to a country's economy. One definition of a bank is an entity whose primary business is to accept deposits from the general public and then make loans, savings accounts, and other financial products and services available to residents of the community in order to raise everyone's quality of living. People's credit banks (BPR) in Indonesia are financial institutions that conduct their operations in accordance with traditional banking practices and/or sharia law. This research set out to quantify the impact of external funding and risk management on the bottom lines of Indonesia's islamic rural banks. From the total sample size of 164 businesses, 46 were selected at random as representative of the banking sector. The Statistical Package for the Social Sciences (SPSS 29) was used for all statistical analyses and data processing. Findings from the study include: (1) the insignificant impact of third-party funds on BPRS performance; (2) the insignificant negative impact of non-performing financing on BPRS performance; (3) the insignificant impact of the financing-to-deposit ratio on BPRS performance; and (4) the significant negative impact of operational costs on BPRS performance.